Cardioprotection after acute exposure to simulated high altitude in rats: Role of nitric oxide - la Padula, Pablo Hugo (2018)
Aim In previous studies, upregulation of NOS during acclimatization of rats to sustained hypobaric hypoxia was associated to cardioprotection, evaluated as an increased tolerance of myocardium to hypoxia/reoxygenation. The objective of the present work was to investigate the effect of acute hypobaric hypoxia and the role of endogenous NO concerning cardiac tolerance to hypoxia/reoxygenation under β-adrenergic stimulation. Methods Rats were submitted to 58.7 kPa in a hypopressure chamber for 48 h whereas their normoxic controls remained at 101.3 kPa. By adding NOS substrate L-arg, or blocker L-NNA, isometric mechanical activity of papillary muscles isolated from left ventricle was evaluated at maximal or minimal production of NO, respectively, under β-adrenergic stimulation by isoproterenol, followed by 60/30 min of hypoxia/reoxygenation. Activities of NOS and cytochrome oxidase were evaluated by spectrophotometric methods and expression of HIF1-α and NOS isoforms by western blot. Eosin and hematoxiline staining were used for histological studies. Results Cytosolic expression of HIF1-α nNOS and eNOS, and NO production were higher in left ventricle of hypoxic rats. Mitochondrial cytochrome oxidase activity was decreased by hypobaric hypoxia and this effect was reversed by L-NNA. After H/R, recovery of developed tension in papillary muscles from normoxic rats was 51–60% (regardless NO modulation) while in hypobaric hypoxia was 70% ± 3 (L-arg) and 54% ± 1 (L-NNA). Other mechanical parameters showed similar results. Preserved histological architecture was observed only in L-arg papillary muscles of hypoxic rats. Conclusion Exposure of rats to hypobaric hypoxia for only 2 days increased NO synthesis leading to cardioprotection.